The Impacts of Financial Inclusion on Economic Development: Cases in Asian‑Pacific Countries - Van, Dinh Thi Thanh; Linh, Nguyen Ha (Comparative Economic Research. Central and Eastern Europe, 2019)
Financial inclusion efforts seek to ensure that all members of an economy can have access to and effectively use appropriate financial services. Improving financial inclusion has become a significant concern for developed and developing countries alike. There are many indicators of financial inclusion, the most elementary of which includes having an account in a financial institution. This paper will evaluate the impact of indicators of financial inclusion on economic development. The result shows that correlations exist between large numbers of bank branches, ATMs, domestic credit in the private sector and the increased rate of development in the economy. People will gain a more prosperous life due to this development. The paper also provides recommendations for the governments of developing countries to improve financial inclusion.